2015
DOI: 10.3892/mco.2015.689
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression levels of p53 and eIF4E markers in histologically negative surgical margins, and their association with the clinical outcome of patients with head and neck squamous cell carcinoma

Abstract: Abstract. Molecular markers can be used to identify residual cancer at the surgical margins of head and neck squamous cell carcinoma (HNSCC) and assist in evaluating the complete resection of the tumour. The purpose of the present study was to investigate the expression levels of prognostic molecular markers at the histological tumour free surgical margins. In the present clinical retrospective study, 24/48 patients were selected with negative surgical margins for further analysis with immunohistochemical stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 21 publications
(28 reference statements)
5
23
0
Order By: Relevance
“…In order to compare the correlation between Thsd7a and common markers of ESCC immunohistochemistry, we performed 4 other indicators of the same patient group (P53, P63, CK5/6, and Ki-67; Figure 1B ). The positive rates and expression localization of these 4 indexes were consistent with previous studies [ 25 29 ], while the positive rate of Thsd7a for ESCC and adjacent normal tissue was 70.1% and 18.2%, respectively (Table 1 ). And the expression of these indicators, suggesting that the cancer of these patients had the characteristic of active proliferation and highly malignant degree of ESCC.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In order to compare the correlation between Thsd7a and common markers of ESCC immunohistochemistry, we performed 4 other indicators of the same patient group (P53, P63, CK5/6, and Ki-67; Figure 1B ). The positive rates and expression localization of these 4 indexes were consistent with previous studies [ 25 29 ], while the positive rate of Thsd7a for ESCC and adjacent normal tissue was 70.1% and 18.2%, respectively (Table 1 ). And the expression of these indicators, suggesting that the cancer of these patients had the characteristic of active proliferation and highly malignant degree of ESCC.…”
Section: Resultssupporting
confidence: 90%
“…Thsd7a is mainly expressed in cell membrane, which is entirely concordant with the previous findings in Membranous Nephropathy [ 23 , 24 ], and there is a little expression in the cytoplasm, which was never sported before. We used P53, P63, CK5/6, Ki-67 as positive control, which showed that the tumor tissues collected were higher malignant ESCC, and the positive rates of the markers were similar with the early reports [ 25 29 ]. The positive rate (70.1%) and positive coincidence rate (55.6%) showed that Thsd7a had higher expression in ESCC of Kazakh patients, Xinjiang.…”
Section: Discussionsupporting
confidence: 71%
“…The phosphorylation of EIF4E is very frequently observed in HNSCC [49]. Moreover, EIF4E is up-regulated in surgical margins of HNSCC patients with local recurrence and could serve as a prognostic biomarker [53]. DeFatta et al indicated that the FaDu cell line displays a high EIF4E protein level and that this is similar to the level observed in patients.…”
Section: Discussionmentioning
confidence: 98%
“…10 p53 mutations in negative surgical margins have been shown to be valuable in predicting local recurrences in head and neck squamous cell carcinoma. [11][12][13] Eukaryotic initiation factor 4E (eIF4E) have a crucial role in control of initial stage protein synthesis. 14 It is the product of a proto-oncogene and carries immense potential as a tumor marker as it has shown overexpression in several epithelial cell tumors and has been reported to be almost 100% overexpressed in HNSCC, breast carcinomas and colon carcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Few retrospective studies have shown that expression of eIF4E at negative surgical margins of HNSCC is useful in predicting local relapse. 13,17 E-cadherin is important for development and maintenance of epithelium and is one of the most essential molecules in cell-to-cell adhesion. 18 The deficit of E-cadherin-mediated cell adhesion associates with the loss of the epithelial morphology and results in invasion of tumor cells.…”
Section: Introductionmentioning
confidence: 99%